2009
DOI: 10.2527/jas.2007-0433
|View full text |Cite
|
Sign up to set email alerts
|

Finishing steers with diets based on corn, high-tannin sorghum, or a mix of both: Feedlot performance, carcass characteristics, and beef sensory attributes1

Abstract: The objective of this work was to compare feedlot performance, carcass characteristics, and beef sensory attributes from steers finished with diets based on corn, high-tannin sorghum (HTS), and a mix of both grains. Angus crossbred steers (n = 11 steers per treatment, initial BW = 404 +/- 18 kg) were finished on diets containing 765 g/kg of DM of corn, HTS, or a 1:1 mix of corn and HTS. Final BW (P < 0.01), ADG (P < 0.001), and G:F (P < 0.01) were reduced in steers fed HTS when compared with steers fed corn. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
2
9
1
1
Order By: Relevance
“…The fat sources used, CSB and SOB at 3 and 5% of EE in the diet, did not affect (P ≥ 0.05) the carcass traits of the animals (Table 4), which is in agreement with Zinn (1989a), Felton andKerley (2004b), Cranston et al (2006), Larraín, Schaefer, Arp, Claus, and Reed (2009),Vander Pol et al (2009, who also found no changes in carcass traits using different fat sources in diets for feedlot cattle.…”
Section: Carcass Evaluationsupporting
confidence: 80%
See 2 more Smart Citations
“…The fat sources used, CSB and SOB at 3 and 5% of EE in the diet, did not affect (P ≥ 0.05) the carcass traits of the animals (Table 4), which is in agreement with Zinn (1989a), Felton andKerley (2004b), Cranston et al (2006), Larraín, Schaefer, Arp, Claus, and Reed (2009),Vander Pol et al (2009, who also found no changes in carcass traits using different fat sources in diets for feedlot cattle.…”
Section: Carcass Evaluationsupporting
confidence: 80%
“…In addition, the values of 55.4 ± 0.22% for HCW/Final BW, 37.0 ± 0.27% for forequarter/HCW, 14.4 ± 0.14% for spare ribs/HCW and 48.6 ± 0.24% for hindquarter/HCW found in this work were close to those reported by Leme et al (2000) for non-castrated Nellore cattle, that found in same traits: 53.7, 40.6, 12.6 and 46.8%, respectively; and by Zorzi et al (2013), who evaluated the effect of residual feed intake in Nellore bulls of similar pedigree to those animals used in this study and found a proportion of forequarter, spare ribs and hindquarter, of 41.2, 12.8 and 46.0, respectively. In terms of cutability proportion, the overall mean was 51.8% cut yields in HCW, a value similar to the 50.5% reported by Larraín et al (2009).…”
Section: Carcass Evaluationsupporting
confidence: 71%
See 1 more Smart Citation
“…Esta situación no sucede cuando se incluye alfalfa, ya que según Otero e Hidalgo (2004) % de taninos, cantidad insuficiente para provocar aversión. Al respecto, Larraín et al (2009) observaron un menor consumo de alimento en toros alimentados con dietas altas en taninos, repercutiendo en una menor ganancia de peso. Adicionalmente, se ha reportado que los ácidos grasos volátiles (AGV) están involucrados en el proceso de consumo de materia seca, particularmente, el propiónico (Loncke et al, 2009;Krizsan y Randby, 2007) que actúa como sustrato fundamental en la gluconeogénesis, proceso por el cual los rumiantes obtienen glucosa a partir de compuestos que no son carbohidratos (Murray et al, 2007).…”
Section: Comportamiento Productivounclassified
“…Sorghum has recently become a popular feed for ruminants in many countries (Oliver et al, 2004;Larraín et al, 2009), including Poland (Pyś et al,…”
Section: Introductionmentioning
confidence: 99%